2023
DOI: 10.1002/jmv.28460
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world effectiveness of sotrovimab and remdesivir for early treatment of high‐risk hospitalized COVID‐19 patients: A propensity score adjusted retrospective cohort study

Abstract: Early treatment of high‐risk COVID‐19 patients may prevent disease progression. However, there are limited data to support treatment of hospitalized or fully vaccinated patients with mild‐to‐moderate disease. In this retrospective cohort study, we studied the effect of early use of sotrovimab and remdesivir in high‐risk hospitalized COVID‐19 patients. We included PCR‐confirmed COVID‐19 patients admitted to the National Centre for Infectious Diseases who presented within the first 5 days of illness, and who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A retrospective study from Israel, among 3761 high-risk patients treated with NMV/r, showed that NMV/r was associated with a greater decrease in the composite end-point of severe COVID-19 and mortality (hazard ratio 0.43, 95% CI 0.85–0.64) [ 22 ]. In a study from Singapore, the authors compared the effectiveness of 3RDV vs. the monoclonal antibody sotrovimab (at the time approved and effective for circulating viral variants) and found that even though 17.8% of remdesivir participants proceeded to require supplemental oxygen when studied after propensity score matching, 3RDV would reduce the danger of hospitalization by 82% [ 23 ]. Larger studies from the US using propensity score matching showed that NMV/r reduced the risk of deterioration by 85% [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study from Israel, among 3761 high-risk patients treated with NMV/r, showed that NMV/r was associated with a greater decrease in the composite end-point of severe COVID-19 and mortality (hazard ratio 0.43, 95% CI 0.85–0.64) [ 22 ]. In a study from Singapore, the authors compared the effectiveness of 3RDV vs. the monoclonal antibody sotrovimab (at the time approved and effective for circulating viral variants) and found that even though 17.8% of remdesivir participants proceeded to require supplemental oxygen when studied after propensity score matching, 3RDV would reduce the danger of hospitalization by 82% [ 23 ]. Larger studies from the US using propensity score matching showed that NMV/r reduced the risk of deterioration by 85% [ 24 ].…”
Section: Introductionmentioning
confidence: 99%